In memory of Kenneth G. Wilson - Wegner, Franz (Journal of statistical physics, 2014)
Kenneth Wilson had an enormous impact on the renormalization group and field theories in general. I had the great pleasure to work in three fields to which he contributed essentially: Critical phenomena, gauge-invariance in duality and confinement, and flow equations and similarity renormalization.